Recursive partitioning to prioritize morphometric traits that separate Aspen specialist Chaitophorus aphid by species and stage - Richa Raizada; Rajarshi Kumar Gaur; Benedicte R. Albrectsen (International Journal of Tropical Insect Science, 2022)

Nutritional niche overlap potentiates the use of endophytes in biocontrol of a tree disease - Kathrin Blumenstein; Benedicte R. Albrectsen; Juan A. Martín; Malin Hultberg; Thomas N. Sieber; Marjo Helander; Johanna Witzell (BioControl, 2015)

Geographic structure in metabolome and herbivore community co‐occurs with genetic structure in plant defence genes - Carolina Bernhardsson; Kathryn M. Robinson; Ilka N. Abreu; Stefan Jansson; Benedicte R. Albrectsen; Pär K. Ingvarsson (Ecology Letters, 2013)
Plant–herbivore interactions vary across the landscape and have been hypothesised to promote local adaption in plants to the prevailing herbivore regime. Herbivores that feed on European aspen ( Populus tremula ) change across regional scales and selection on host defence genes may thus change at comparable scales. We have previously observed strong population differentiation in a set of inducible defence genes in Swedish P. tremula . Here, we study the geographic patterns of abundance and diversity of herbivorous insects, the untargeted metabolome of the foliage and genetic variation in a set of wound‐induced genes and show that the geographic structure co‐occurs in all three data sets. In response to this structure, we observe local maladaptation of herbivores, with fewer herbivores on local trees than on trees originated from more distant localities. Finally, we also identify 28 significant associations between single nucleotide polymorphisms SNP s from defence genes and a number of the herbivore traits and metabolic profiles.

Global regulatory burden for field testing of genetically modified trees - Venkatesh Viswanath; Benedicte R. Albrectsen; Steven H. Strauss (Tree Genetics & Genomes, 2012)

Variation in protein complexation capacity among and within six plant species across a boreal forest chronosequence - Michael J. Gundale; Jennie Sverker; Benedicte R. Albrectsen; Marie-Charlotte Nilsson; David A. Wardle (Plant Ecology, 2010)

Natural phenological variation in aspen (Populus tremula): the SwAsp collection - Virginia Luquez; David Hall; Benedicte R. Albrectsen; Jan Karlsson; Pär Ingvarsson; Stefan Jansson (Tree Genetics & Genomes, 2008)